CHARACTERS, DETERMINANTS, AND ASSOCIATION BETWEEN CHRONIC ANEMIA AND ATRIAL FIBRILLATION: CASE–CONTROL STUDY - MOHAMMED, HAIDER SHAHEED (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was carried out to study the characters, determinants of anemia among atrial fibrillation (AF) patients and to estimate the link between chronic anemia and AF. Methods: This is a case–control study, administrated in Al-Hussein Teaching Hospital among admitted patients in the cardiac care unit from 1st week of January 2018 to the last week of April 2019. A random sample of 100 patients was included in the study based cut of time, where a special form of inquiry sheet was constructed to gather data and it was reviewed and revised by matter experts for testing the validity and enrichment of it. Both cases of AF and control with sinus rhythm were divided into anemic and non-anemic, anemia is defined as hemoglobin <13 and <12 in male and female, respectively. A Statistical Package for the Social Sciences (SPSS) version (25) was used for data analysis. Descriptive statistics Chi-square Fischer exact test, and ANOVA tests of significance, correlation and logistic regression analysis had been estimated where p<0.05 was set as statistically significant. Results: A total of 100 individuals had been included in the study, 50 cases with AF and 50 control with mean of age was 62.74003±13.424 years 58 females with 42 males, total non-anemic was 57 while total anemic was 43, 74.4% of AF cases was anemic while 25.6% of control group was anemic, there was statistically significant difference between cases and control according to the presence and absence of anemia where p<0.05. Conclusion: The first study done in the region to prove the direct relation of anemia on incident AF, thus in conclusion, chronic anemia had a relation with AF.